DIALEKTIKA AKAL DAN WAHYU DALAM PEMBENTUKAN FATWA SERTA REGULASI LINGKUNGAN DI INDONESIA - Attas, Nasrah Hasmiati; Kurniati, Kurniati; Mustafa, Zulhas'ari (IAIN BONE, 2025)
The escalating complexity of environmental degradation has prompted various normative approaches, including those informed by Islamic thought. This article explores the dialectical relationship between reason (â€˜aql) and revelation (wahy) in the formulation of environmental fatwas and legal regulations in Indonesia. It further examines the extent to which the localization (pembumian) of Islamic values reflects epistemological harmony or tension between these two foundational sources. Employing a literature-based qualitative method, the study analyzes selected fatwas issued by the Indonesian Council of Ulama (MUI), national environmental legislation, and key Islamic scholarly works. The findings reveal that environmental fatwas are shaped not only by normative scriptural texts but also by rational responses to empirical ecological challenges. In parallel, state regulationsâ€”though secular in structureâ€”frequently resonate with Islamic ethical principles, particularly those within the framework of maqÄá¹£id al-sharÄ«â€˜ah. This convergence suggests that reason and revelation can operate complementarily rather than in opposition. However, institutional and epistemological gaps remain, especially in integrating religious moral authority with actionable public policy. Strengthening interdisciplinary collaboration between religious scholars, academics, and policymakers is therefore essential for the advancement of a contextually grounded Islamic environmental jurisprudence.